Peran Dosen Penasehat Akademik (PA) Prodi Perbankan Syariah Jurusan Syariah dan Ekonomi Islam STAIN Curup Dalam Menangani Permasalahan Mahasiswa - Busra Febriyarni (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2018)
This paper raises the issue of how the role of PA lecturers in solving problems of students of Islamic banking study programs majoring in Sharia and Islamic Economics. The method used in this study is field research with a qualitative descriptive approach. The source of important data in this study is the PA lecturer in the Sharia Banking study program which is also called the research informant. The results showed that students had many academic problems, including the problem of taking courses every semester there were pre and no conditions, shortages and excess credits, less cooperative or less familiar with their respective PA lecturers, problems, economics, family there are even personal problems that consult with PA lecturers. The role of PA lecturers in solving the problem of the students in the Islamic Banking study program is quite well, this can be seen from the role of PA lecturers as their student mentors in academic matters that lead to taking courses, as advisors who always remind students in several ways, such as ethical issues , not yet fluent in reading Al-Quran, and as a motivator who always gives motivation to a better future career, their parents' economic problems and their relationship to the late payment of semester fees and others. In general, PA lecturers in the Sharia banking study program have played a role as PA lecturers both as mentors, directors, advisors and motivators in the academic, social, economic and career fields.